2001
DOI: 10.1055/s-2001-11582
|View full text |Cite
|
Sign up to set email alerts
|

Wie beurteilen psychisch kranke Wohnungslose ihre Lebensqualität?1

Abstract: Besides pronounced deficiencies in psychiatric research concerning homeless mentally ill in Germany, studies concerned with the quality of life of homeless mentally ill were missing until now. This study reveals in a representative sample of 102 homeless people from the City of Mannheim, Germany that--compared to the homeless without psychiatric disorders of the sample--the mentally ill homeless (prevalence 68.6%) have significantly different subjective views of their quality of life regarding the items "state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
2
Order By: Relevance
“…To our knowledge, this is the first study to comprehensively evaluate HS across all housing situations of mentally ill people, rather than simply homeless vs. domiciled. As hypothesized, the results demonstrate a decrease in HS when the housing situation becomes less normative, which contributes to findings of other studies (12,14,19,25). HS was found to be significantly higher for domiciled and shared-flat categories, than facilities, and finally, people in the homeless category reported the lowest satisfaction.…”
Section: Discussion Main Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, this is the first study to comprehensively evaluate HS across all housing situations of mentally ill people, rather than simply homeless vs. domiciled. As hypothesized, the results demonstrate a decrease in HS when the housing situation becomes less normative, which contributes to findings of other studies (12,14,19,25). HS was found to be significantly higher for domiciled and shared-flat categories, than facilities, and finally, people in the homeless category reported the lowest satisfaction.…”
Section: Discussion Main Findingssupporting
confidence: 85%
“…Previous studies on QoL in regard to housing circumstances showed that homeless persons and psychiatric patients, but most strikingly homeless people with a mental disorder report a significantly lower QoL than the general population (5,9,17). Additionally, homeless mentally ill samples reported lower QoL in several life domains, including finances, friends and family, as compared to domiciled and community-based care patients (19,25,26).…”
Section: Introductionmentioning
confidence: 90%
“…The mean ages of the investigated homeless people ranged from 29 to 48.1 years. Five studies were conducted in Munich (n = 804) (2, 11, 27, 29, 31-39, e1), two in Tübingen (n = 108) (22,30), and one each in Berlin (n = 72) (28,40), Münster (n = 52) (26), Mannheim (n = 102) (23)(24)(25), and Dortmund (n = 82) (12,21). For the longitudinal study conducted in Munich, analysis took account of when data was first collected (27,36).…”
Section: Resultsmentioning
confidence: 99%
“…Um im Rahmen der o. g. Problemfelder weiterführende Erkenntnisse über psychiatrische und/oder psychosoziale Belastungen im Vorfeld zur Wohnungslosigkeit zu erlangen, wurden nach einer Reihe von in der Vergangenheit in Mannheim (Baden-Württemberg) durchgeführten Studien im Problemfeld psychischer Störungen und Wohnungslosigkeit [38,39] …”
Section: Ziele Der Untersuchungunclassified